ANALYSIS OF POLYMORPHISM OF THE GENES OF THE PHASE II OF XENOBIOTICS BIOTRANSFORMATION (GSTM1, GSTT1) IN THE SHORIANS AND ALIEN POPULATION OF THE KEMEROVO REGION: THE PROBLEM OF THE DIFFERENCES IN MORTALITY RATE FROM MALIGNANT NEOPLASMS - Фаина Анисимовна Лузина; Анастасия Викторовна Дорошилова; Владимир Юрьевич Смирнов; Анастасия Сергеевна Казицкая; Ольга Николаевна Гуляева; Татьяна Константиновна Ядыкина; Анатолий Владимирович Колбаско (Медицина в Кузбассе, 2017)
Subject. Polymorphism of the genes of xenobiotics biotransformation GSTM1, GSTT1 (probable markers of cancer risk) in the Shorians and Europeoid population of the Kemerovo Region; mortality rates from malignant neoplasms (MNP) in the Shorians and the entire population in Novokuznetsk for the period from 1970 to 1999.